Design and Construction of a Web-Based Information System for Product Performance Monitoring and Inventory Management at John Store - Farras Fadhlur Rohman; Nining Rahaningsih; Bani Nurhakim (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
It must be able to stand alone since abstracts are frequently given apart The utilization of information technology has developed into a vital instrument in enhancing operational efficiency and business competitiveness, particularly in the medium-scale retail sector. Accurate inventory management is the primary foundation for business sustainability to maintain consistent customer satisfaction. However, John Store currently faces complex operational obstacles as it relies entirely on manual recording methods. The absence of a structured internal database system causes significant data synchronization issues between administrative records and physical stock in the warehouse, thereby increasing the risk of sudden stockouts. The most fundamental and crucial issue lies in managing bundling category products, where a single package transaction often fails to accurately deduct the stock balance of individual components due to the high risk of human error in manual calculation. To address this inefficiency, this research aims to build the web-based John Store Information System (SIJOHNS) as an integrated internal back-office solution. System development applies the Waterfall method systematically, covering requirements analysis, system design through Flowmap, Data Flow Diagram (DFD), and Entity Relationship Diagram (ERD), to implementation using PHP programming language and MySQL database. Key system features include the automation of bundling stock mapping and multi-role access rights management. Based on Black Box Testing, the system is proven valid. The implementation of SIJOHNS successfully transforms inventory management into a digital format, ensures the accuracy of stock deduction in real-time, and presents analytical data visualization on the dashboard to facilitate the store owner in monitoring sales trends for more strategic and targeted business decision-making